If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26-9p=1
We move all terms to the left:
26-9p-(1)=0
We add all the numbers together, and all the variables
-9p+25=0
We move all terms containing p to the left, all other terms to the right
-9p=-25
p=-25/-9
p=2+7/9
| -4(8x+2)=-1-5(-6x+6) | | X^2+12x+4x^2+9=36 | | X^2+(2x+3)^2=36 | | -2w+1=3 | | X+8=1x | | X+8=1x+0 | | g/25+4=3.8 | | 35a+4-15a=21a+5 | | -1-7(x+7)=-7-(3+3x) | | -1-7(x+7)=-7-(3+5x) | | 8+9x-18=-1x+8 | | 3x+4.75=11.50 | | -12x+4=2x+10 | | -6+41/2b=18 | | 75p-7=21 | | 5x-7+2x+18=00 | | 5x-7+2x+18=136 | | 6x+2/16=6x+17/28 | | 6^4x-8=1 | | -5x+3=-35 | | 6x-14=109 | | 4x+13=6x-14 | | 3(8a−2)=6(5+3a) | | 90+34=180-x-72 | | y=40-1 | | y=-4-1-1 | | 6+3(2v-2)=-2(9v-1)=6v | | (2x-20)=(x+10) | | 2(4x+4)=-2(x+5) | | (2x-20)=(x+10 | | 12+t5(t-6)=4 | | X+10=6x+3 |